(untitled) (Princeton, 2008)
Red State, Blue State, Rich State, Poor State is a must-read for anyone seeking to make sense of today’s fractured American political landscape.
Keywords: Elections,Elections,Politics, Practical,Chính trị, thực hành,Bầu cử; United States.,United States,United States,Hoa Kỳ,Hoa Kỳ